A Meta-Analysis of Antecedents and Correlates of Employee Turnover: Update, Moderator Tests, and Research Implications for the Next Millennium - Griffeth, Rodger W.; Hom, Peter W.; Gaertner, Stefan (Journal of Management, 2000)
This article reports the results of a comprehensive meta-analysis of turnover antecedents, extending an earlier one by Hom and Griffeth (1995). As such, this updated meta-analysis represents the most wide-ranging quantitative review to date of the predictive strength of numerous turnover antecedents. Importantly, the present investigation identifies various moderators of antecedent-turnover correlations. The implications of these findings for both theory and practice are discussed.